Generic qualitative research: a design for qualitative research in emergency care?. Issue 12 (20th November 2007) - Cooper, S; Endacott, R
Abstract : The frequency of qualitative studies in the Emergency Medicine Journal, while still low, has increased over the last few years. All take a generic approach and rarely conform to established qualitative approaches such as phenomenology, ethnography and grounded theory. This generic approach is no doubt selected for pragmatic reasons but can be weakened by a lack of rigor and understanding of qualitative research. This paper explores qualitative approaches and then focuses on "best practice" for generic qualitative research.